2013
DOI: 10.4314/ahs.v13i2.30
|View full text |Cite
|
Sign up to set email alerts
|

Condom use at first and latest sexual events among young people: evidence from a rural and peri-urban setting in Uganda

Abstract: Background: Condom use remains low among young people despite high prevalence of HIV, STIs, and unplanned pregnancy in Uganda. Objectives: This paper presents patterns of condom use at first and latest sexual events and associated factors. Methods: The data were obtained from 445 sexually active unmarried people aged 15-24 from one peri-urban and another rural district. Stratified multi-stage cluster sampling technique was applied. Logistic regression was used to identify factors associated with condom use at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The timing of these HIV-associated vulnerabilities and a woman's first sexual experience may influence her HIV risk. 4 Early age at first sex (often defined as <15 years of age 5 ) is associated with increased risk of bacterial sexually transmitted infections partly due to cervical ectopy in adolescence, 6 , 7 higher levels of inflammatory cytokines in the female genital tract, 8 , 9 less condom use at first sex and subsequent sex acts, 10 , 11 and prevalent HIV infection. 4 , 12 AGYW who reach menarche and puberty early are more likely to engage in earlier (and often condomless) sexual activity than those who experience later menarche.…”
Section: Introductionmentioning
confidence: 99%
“…The timing of these HIV-associated vulnerabilities and a woman's first sexual experience may influence her HIV risk. 4 Early age at first sex (often defined as <15 years of age 5 ) is associated with increased risk of bacterial sexually transmitted infections partly due to cervical ectopy in adolescence, 6 , 7 higher levels of inflammatory cytokines in the female genital tract, 8 , 9 less condom use at first sex and subsequent sex acts, 10 , 11 and prevalent HIV infection. 4 , 12 AGYW who reach menarche and puberty early are more likely to engage in earlier (and often condomless) sexual activity than those who experience later menarche.…”
Section: Introductionmentioning
confidence: 99%
“…Sample populations included refugees from Sudan, the Democratic Republic of Congo, Somalia, Burundi, Iraq and Bhutan. n/a n/a Toska et al, 2020 63 Quantitative, Cross-sectional 10–24 Females South Africa Mixed Random and purposive Tumwesigye et al, 2013 64 Quantitative, Cross-sectional 15–24 Males and females Uganda Mixed Multi-stage cluster Wado et al, 2020 65 Scoping review 10–19 Males and females Sub-Saharan Africa n/a n/a Wong et al, 2017 66 Qualitative, Cross-sectional 11–19 Males and females China Rural Purposive Ziraba et al, 2018 67 Quantitative, Cross-sectional 12–23 Females Kenya Urban Random a At the time of this study, participants’ age varied from 18 to 35 years; however, their adolescent experiences were explored. b Age-disaggregated data for adolescents available.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly in another part of the world, the findings of a study on young adults' sexuality in Peru showed that 38 % of male youths adhered to condom usage the first time that they had intercourse [24]. In Uganda, the prevalence of condom usage at the first sexual intercourse among young adults who are unmarried is reported to be 37 % for female and 59 % for males [25].…”
Section: Literature Reviewmentioning
confidence: 99%